EXPLORING ENGLISH FOREIGN LANGUAGE STUDENTS’ LEARNING STRATEGIES IN READING ELT MATERIALS - Rahayu Meliasari (Universitas Perjuangan Tasikmalaya, 2019)
This research aimed to reveal the type of language learning strategies dominantly used by the learners and the least type of learning strategies used by the learners. There were 10 students who were taken as the sample of participants. They are students who officially enrolled in Academic Reading Class in the second semester of English Study Program of Teacher Training and Education Faculty (FKIP) Tanjungpura University in Academic Year 2016/2017. Questionnaire consisting of 40 statements was distributed for data collection which in turn were analyzed by using mean score calculation. The analysis of the data revealed that the mean score of metacognitive learning style was 4.0 which indicated that this type of learning strategy fell into the highest frequency used by the students. Meanwhile, the average score for cognitive strategies was 3.7 in which it is categorized as the second rank of the learning strategy mostly used by the learners. The analysis toward compensation strategy resulted 3.5 for the mean score, and the average score for affective and social strategy reached average at 3.1 and 3.0 respectively. By contrast, memory strategy is the least type of learning strategy used by the students, reaching the mean only at 2,9.Keywords:Â EFL,Â Language Learning Strategies, Reading, ELT Materials